Pengaruh Profitabilitas, Perputaran Aset, Solvabilitas, Dan Kebijakan Dividen Terhadap Tingkat Pertum-buhan Berkelanjutan - Klarisa Giovani; Mardiati, Endang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The sustainable growth rate is the maximum growth rate that can be achieved by the company without having to increase capital from shareholders and attract creditors. This study was conducted to examine and analyze the determinants of sustainable growth rates, namely net profit margin, total asset turnover, debt-to-equity ratio, and dividend payout ratio. The object of this research is the pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2015 – 2020 selected through purposive sampling. This research is an explanatory research type with a quantitative approach. The research data is secondary data in the form of annual financial statements of related companies. The analytical tool used is multiple linear regression analysis with SPSS 24 application. The results show that total asset turnover (TATO) has a positive effect on sustainable growth rates. Net profit margin (NPM), debt-to-equity ratio (DER), and dividend payout ratio (DPR) have no effect on the sustainable growth rate.